Scanning electron microscopic evaluation of the successful sterilization of Lucilia cuprina (Wiedemann) utilized in maggot debridement therapy (mdt) - Yeong, Y.S.; Nazni, Wasi Ahmad; Santana, R.L.; Mohd Noor, I.; Lee, H.L.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2011)
In Malaysia, maggot debridement therapy (MDT) utilizes maggots of Lucilia cuprina (Wiedemann) to debride necrotic tissue from wound surface, reduce bacterial infection and therefore, enhance wound healing process. To evaluate the sterility of the sterile maggots produced after sterilization process before delivering onto patient wounds. Sterility of sterile maggots is crucial in ensuring the safe usage of MDT and patient’s health. Eggs of L. Cuprina collected from a laboratory colony were divided into treated group (sterilized) and control group (non-sterilized). Treated group underwent sterilization while eggs from control group were allowed to hatch without sterilization. Sodium hypochlorite and formaldehyde were the main disinfectants used in this sterilization process. Scanning electron microscope (SEM) was used to examine and ascertain the sterility of sterile maggots. SEM results showed that all sterilized L. cuprina eggs and maggots achieved sterility and all were cleared from bacterial contamination. In contrast, all non-sterilized eggs and maggots were found to be colonized by microorganisms. Sterilization method employed to sterilize eggs and maggots used in Malaysia MDT was proven successful and MDT is safe to be used as wound management tools.